2015
DOI: 10.1074/jbc.m114.627356
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Distinct Conformations of the Angiotensin-II Type 1 Receptor Associated with the Gq/11 Protein Pathway and the β-Arrestin Pathway Using Molecular Dynamics Simulations

Abstract: Background: The N111G and D74N mutations bias the AT 1 receptor for the G q/11 and ␤-arrestin pathways, respectively. Results: Structural rearrangements of theAT 1 receptor are induced by the N111G mutation and AngII. Conclusion: Activation of the G q/11 and ␤-arrestin pathways is associated with a decreased and increased stability, respectively, of the ground state of the receptor. Significance: Distinct conformations of AT 1 receptor are associated with distinct pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 80 publications
1
34
0
2
Order By: Relevance
“…This could explain the reduced potency and efficacy of [Sar 1 Hcy 3,5 ]AngII on the Gq pathway. The importance of Phe 8 of AngII for Gqmediated signaling is well documented and we have previously linked its insertion within the hydrophobic core to the activation of the Gq pathway [19,37,40]. The data obtained in the current study suggest that the energy barrier that needs to be overcome for the insertion Thus, when compared to the β-strand and extended conformations, the g-turn conformation of AngII, to which the cyclic analog is confined, is less effective at stabilizing the Gqactive state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could explain the reduced potency and efficacy of [Sar 1 Hcy 3,5 ]AngII on the Gq pathway. The importance of Phe 8 of AngII for Gqmediated signaling is well documented and we have previously linked its insertion within the hydrophobic core to the activation of the Gq pathway [19,37,40]. The data obtained in the current study suggest that the energy barrier that needs to be overcome for the insertion Thus, when compared to the β-strand and extended conformations, the g-turn conformation of AngII, to which the cyclic analog is confined, is less effective at stabilizing the Gqactive state.…”
Section: Discussionmentioning
confidence: 99%
“…We next generated a complex between AngII and AT1R by docking our previously established model of AngII bound to a homology model of the AT1R [17,37] onto the threedimensional crystal structure of the AT1R [2]. One microsecond of MD simulation time was initially performed on the AngII-AT1R complex in the form of ten trajectories each This is the postprint version of the following article: St-Pierre D, et al (2018), Biochem Pharmacol.…”
Section: Simulations Of the Angii-at1r Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that a mutation of the equivalent residue in the AT 1 receptor (N111G) and CXCR4 receptor (N119S) results in constitutive activation and that the residue in addition functions as an anchor site for binding of the endogenous agonist in the former receptor (Noda et al, ; Berchiche et al, ). Interestingly, a recent molecular dynamics simulation suggested that N111 keeps the AT 2 receptor in an inactive conformation through hydrogen bonds with the Asp at II:10 (Cabana et al, ). Moreover, as suggested by a new crystal structure, this probably also involves a sodium ion (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cabana e colaboradores utilizaram um modelo de homologia do receptor AT1 e observaram padrões de RMSD distintos no segmento Asn288 (Bihoreau et al, 1993). É postulado que a ocupação do sitio de ligação pela AngII desestabiliza a ligação de hidrogênio Asn111 3.35 -Asn295 7.46 , permitindo que a Asn295 7.46 /Tyr292 7.43 façam uma ligação de hidrogênio com o Asp74 2.50 (Marie et al 1994, Groblewski et al 1997, Inoue et al 1997 (Cabana et al, 2013, Cabana et al, 2015. Nas nossas simulações com a AngII observamos ligações de hidrogênio entre Asp74 2.5 -Asn295 (Dror et al 2011, Rovati, et al 2007.…”
Section: Angiotensina IIunclassified